2020
DOI: 10.1364/ol.403135
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive-glasses time-domain FFOCT for wide-field high-resolution retinal imaging with increased SNR

Abstract: The highest three-dimensional (3D) resolution possible in in vivo retinal imaging is achieved by combining optical coherence tomography (OCT) and adaptive optics. However, this combination brings important limitations, such as small field-of-view and complex, cumbersome systems, preventing so far the translation of this technology from the research lab to clinics. In this Letter, we mitigate these limitations by combining our compact time-domain full-field OCT (FFOCT) with a multi-actuator adaptive lens positi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…2) occurs at a larger spatial frequency cutoff than in the incoherent image. These observations seem to indicate a low sensitivity of FFOCT with respect to defocus, which is in good agreement with previous experimental observations [18,19,23].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2) occurs at a larger spatial frequency cutoff than in the incoherent image. These observations seem to indicate a low sensitivity of FFOCT with respect to defocus, which is in good agreement with previous experimental observations [18,19,23].…”
Section: Resultssupporting
confidence: 93%
“…Whether it be recorded in the time or spectral domains, studying the impact of aberrations on the FFOCT image formation is crucial to understand how to incorporate efficient adaptive optics [18,19] or post-processing computational tools [14,20,21] in FFOCT [22]. Indeed, system-induced and sample-induced aberrations are the main fundamental limits in the quest for a diffraction-limited resolution, a high sensitivity and a large penetration depth.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as in the structured-illumination ophthalmoscope the super-resolution is limited by the contrast, using the partial-field illumination ophthalmoscope would allow one to achieve even higher super-resolution, since the achievable super-resolution directly depends on the SNR [23]. Finally, the partial-field illumination ophthalmoscope approach could also be a valuable concept to full-field optical coherence tomography (FF-OCT) imaging systems applied for retinal imaging [24][25][26]. The use of the partial-field illumination ophthalmoscope, in fact, could reduce cross-talk (in coherent illumination) [27], and/or incoherent light level detected by the 2D camera, contributing to an…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that axial motion suppression works as long as residual axial motion after correction is smaller than the temporal coherence gate width [22,23]. In FFOCT high-resolution in vivo retinal imaging, a temporal coherence gate of 8 µm is used [10]. Therefore, if we approximate the temporal fluctuation of retinal axial motion as a Gaussian distribution, one can establish that an RMS error below 4 µm will ensure a residual axial motion of amplitude lower than the 8 µm coherence gate width more than 95% of the time.…”
Section: B Axial Tracking Loop Simulationmentioning
confidence: 93%
“…By exploiting this phenomenon, we were able to apply FFOCT for high 3D resolution imaging of the living human retina. This achievement was possible owing to recent advances in FFOCT, including shaping the temporal coherence gate to match the retina curvature, achieving a wide field-of-view (5°× 5°) [8], stabilizing the axial retinal motion in real-time [9], and increasing signal-to-noise ratio (SNR) using the adaptive-glasses approach for ocular aberration correction [10]. Given its relative simplicity and small footprint, FFOCT holds promise for adoption by clinicians [11].…”
Section: Introductionmentioning
confidence: 99%